Quantitative Determination of Nitrendipine in Human Plasma Using High-performance Liquid Chromatography-Mass Spectrometry - Liu, Ying; Xu, Feng-guo; Zhang, Zun-jian; Song, Rui; Tian, Yuan; Chen, Yun (Arzneimittelforschung, 2008)
A sensitive and highly selective liquid chromatography-mass spectrometry (LC-MS) method was developed to determine nitrendipine (4-dihydro-2,6-dimethyl-4-(3-nitrophenyl)-3, 5-pyridinedicarboxylic acid ethyl methyl ester, CAS 39562-70-4) in human plasma. The analyte and the internal standard nimodipine (CAS 66085-59-4) were extracted from plasma samples by n-hexane-isopropanol (95:5, v/v), and analyzed on a commercially available column interfaced with a mass spectrometer. Positive atmospheric pressure chemical ionization (APCI) was empolyed as the ionization source. The samples were detected by the use of selected ion monitoring (SIM) mode. The mobile phase consisted of methanol-water (75:25, v/v). The method has a limit of detection (LOD) of 0.1 ng/ml. The linear calibration curves were obtained in the concentrations range of 0.3–40 ng/ml (r2≥0.99). The intra- and inter-day batch precisions were lower than 10% in terms of relative standard deviation (R. S. D.), and the accuracy ranged from 85 to 110% in terms of percent accuracy. The overall extraction recoveries were determined to be about 75% on average. This validated method was successfully applied to the evaluation of the pharmacokinetic profiles of nitrendipine tablets administered to 8 Chinese healthy volunteers.
Keywords: Calcium antagonists, 1,4-dihydropyridine; CAS 39562-70-4; Nitrendipine, bioavailability, LC-MS method, pharmacokinetics